The future of international business research: theorizing on unfolding phenomena in a complex dynamic world - Zettinig Peter; Nummela Niina (Edward Elgar Publishing, 2022)
This chapter takes a futures-oriented perspective to International Business as a field of inquiry. The transitionary nature of complex dynamic systems challenges our understanding of the world and forces us to reconsider our explanations. As the world changes continuously and often in disruptive ways, we ask how to develop theories that can evolve with such changes and how this may enhance IB research’s utility. To increase relevance, we discuss how examples of mainstream IB frameworks, as widely shared reference points, can serve as a baseline to advance practice-oriented questions into research questions. We envision a critical-realist approach as a theorising vehicle that produces possible explanations for currently unfolding phenomena.
A Research Agenda for International Business and Management